Pengembangan Aplikasi Sistem Informasi Geografis (SIG) berbasis Web untuk Manajemen Pemanfaatan Air Tanah menggunakan PHP, Java dan MySQL Spatial (Studi Kasus di Kabupaten Banyumas) - Jumadi, J; Widiadi, Sigit (Universitas Muhammadiyah Surakarta, 2009)
In the existing world of geographic information systems (GIS), desktop mapping has taken a critical role for managing and using spatial information for business. But desktop-based GIS application having any limitation for users. The research was conducted to develop the web-based GIS in order to manage groundwater exploration and production, preventing from uncontrolled exploration, using Java Applet, MySQL Spatial and PHP. The system development was designed by using waterfall model of system life cycle with following steps: 1) system requirements, 2) software requirements, 3) analysis, 4) program design, 5) coding, 6) testing, and 7) operation, supported by reference study, observation, and peer discussion. The result shows that by using Java Applet, MySQL Spatial and PHP, web-based GIS for groundwater management is customizable to create spatial modeling and well log modeling, user friendly, interactive, interoperable, informative, and easy to access with LAN/WAN connected PC. The application is very helpful in order to balance between groundwater supply and production, groundwater level monitoring, water quality monitoring, and groundwater user monitoring. Hopefully, the implementation of the system will help the groundwater supply conservation for sustainable development.